Child problem behaviours are associated with obesity in parents caring for children with developmental disabilities. (January 2015) - Gallagher, Stephen; Hannigan, Ailish
Highlights: Parents of children with disabilities are at an increased risk of obesity. The excess risk was independent of their psychological and physical health status. Child problem behaviours were key determinants of obesity in these parents. Abstract: Epidemiological evidence suggests that obesity and depression are highly co-morbid. In a national cohort study, we examined whether parents caring for children with disabilities were more likely to be classified as obese compared to parents of children without disabilities and if obesity was associated with depressive symptoms or child behaviour characteristics. Using data from the Growing Up in Ireland National Longitudinal Study of Children (2006 to date), 627 parents of children with developmental disabilities were compared with 7941 parents of typically developing children on objectively measured levels of obesity (body mass index ≥30 kg/m 2 ), depression, health behaviours, chronic health conditions, socio-demographic and child behavioural characteristics. Parents of children with disabilities were more likely to be classified as obese compared to control parents (24.5% vs. 19.6%, p  = 0.005, Cramer's V  < 0.1). Depression was not associated with obesity. However, the odds of obesity increased with increasing child problem behaviour (OR 1.05, 95% CI 1.03–1.06). Over half (57%) of obese parents caring for children with disabilities reported trying to lose weight often or very often. This study has confirmed, in a population-based sample, the high risk of obesity in parents caring for children with disabilities after adjusting for the presence of depression and other health behaviours; increasing child problem behaviours were predictive of obesity. Importantly, given the negative health correlates of obesity, it is imperative that health professionals pay attention to weight issues in these parents and support their efforts in managing these issues.